The Role Of Murobbi In Incorporating Adab In Students: An Evaluative Case Study In Subang Islamic Boarding School - Beni Suwardi (DAAR EL-KAMIL: Multidisciplinary Journal, 2026)
This study aims to definitively formulate and comprehensively evaluate the role of Murobbi (close mentors/dormitory supervisors) in instilling adab (Islamic etiquette and morality) among students at Pesantren Subang. Amidst the rapid waves of modernization and digitalization that trigger various moral degradation phenomena among the younger generation, Islamic boarding schools (pesantren) consistently uphold the universal principle of prioritizing adab before knowledge. Utilizing a qualitative approach with a descriptive analysis method, this study positions the author as the primary instrument conducting direct participatory observations and intensive in-depth interviews with the Murobbi board and students at Pesantren Subang. The results indicate that the Murobbi plays a pivotal role transforming into three strategic functions: as Uswah Hasanah (a conceptual living role model), an embedded mentor (through psychological-spiritual approaches), and a dynamic daily behavior evaluator. The integration of this strategy is empirically proven to significantly improve the quality of students' adab towards teachers, peers, and the environment. This study concludes that strengthening the function of close mentors (Murobbi) is an absolute prerequisite for the successful internalisation of character values and moral revitalization in contemporary Islamic educational institutions.